Public–private partnership (PPP): theory of the issue and world experience in implementing PPP projects - A. N. Rodionov; M. A. Dyakonova (Путеводитель предпринимателя)
The public–private partnership aims on a contractual basis to develop a property complex owned by the State by right. However, the influence of private business should not be underestimated, as it is often the initiative of private organizations in the desire to influence some problems in various spheres lead to effective interaction between the state and business. Investment is an integral part of public–private partnerships. Many people, despite the rapid steps forward of modern society, associate investment with very complex financial processes. Investment in its essence is a tool that benefits participants of investment cooperation.The subject of this study is the definition, on the basis of the theory of public–private partnership, of the main trends in PPPs in the world and in Russia. The authors substantiated that infrastructure, especially in the case of our country, is one of the key areas of PPP development, along with environmental conservation and balanced use of all types of resources. The world is constantly in motion, and many examples and experiences are currently irrelevant or questionable. We need to look at this issue from the experience of other countries and specific enterprises.